2016
DOI: 10.1080/10410236.2015.1072124
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of U.S. Chain Restaurant Food Consumption and Obesity in China and South Korea: An Ecological Perspective of Food Consumption, Self-Efficacy in Weight Management, Willingness to Communicate About Weight/Diet, and Depression

Abstract: This study examined the impact of U.S. chain restaurant food consumption in China and South Korea from an ecological perspective. Specifically, it explored the relationships among several environmental and individual variables that have been found to affect obesity/weight management in previous research, including the prevalence/popularity of U.S. chain restaurants in these countries, frequency of U.S. chain restaurant food consumption, self-efficacy in weight management, willingness to communicate about weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…Moreover, the obesity prevalence rate in South Korea is also increasing, growing 2.6% annually on average from 1998 to 2016 [ 1 ]. The growth of the restaurant industry and the increasing rate of obesity are highly correlated, and scholars, policymakers, and marketers are carefully considering this situation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the obesity prevalence rate in South Korea is also increasing, growing 2.6% annually on average from 1998 to 2016 [ 1 ]. The growth of the restaurant industry and the increasing rate of obesity are highly correlated, and scholars, policymakers, and marketers are carefully considering this situation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fast food diet and sedentary behavior may lead to obesity and overweight status. On the other hand, obesity and overweight are affected by many factors, including genes, individual choice [ 4 ], obesity self-awareness [ 6 ], and personal dietary preferences [ 7 ]. Various factors jointly shape a person’s way of life and hence affect the person’s weight.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in the USA showed that high consumption of restaurant and buffet foods increased the risk of obesity, indicating a relationship between easy access to local restaurants and diet and high BMI [23]. In a longitudinal study, Wright et al [24] reported that consumption of restaurant food once a week significantly increased likelihood of overweight compared to those that did not consume restaurant food at all. Moreover, buying food for the family from restaurants once a week also increased mean percentage of body fat and incidence of cardiovascular diseases [24].…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal study, Wright et al [24] reported that consumption of restaurant food once a week significantly increased likelihood of overweight compared to those that did not consume restaurant food at all. Moreover, buying food for the family from restaurants once a week also increased mean percentage of body fat and incidence of cardiovascular diseases [24]. Frequent consumption of ready-made foods by adults is associated with increased BMI and body weight and increased body weight affects insulin resistance over time and metabolic outcomes [25,26].…”
Section: Discussionmentioning
confidence: 99%